Penerapan Metode UCD (User Centered Design) Pada Sistem Perpustakaan Sekolah Berbasis Android - Berkah Fadli Nur Ramadlan; Sri Wulandari; RR. Hajar Puji Sejati; Agus Suhendar (STMIK Budi Darma, 2024)
SMPN 1 Rembang is located in Losari Village, Rembang District, Purbalingga Regency. The library of SMPN 1 Rembang in carrying out its duties is still conventional such as recording in a book filling in the visitor list, borrowing and returning books. Systems that run manually often get problems such as problems that often occur books that are often returned late. This research discusses the design of an online book loan system by utilizing internet technology which is growing rapidly. This application is used to make it easier for students and teachers when borrowing books because there is no need to come directly to the library so that every process carried out becomes more effective. The method used in system development is the User Centered Design (UCD) method, in this development method there are 4 stages of the approach, namely analysis, design, evaluation, and implementation. PHP is used as a development tool in this research, namely as a programming language and MySQL as a database. The results of the research obtained while in the form of an online book lending system that can run according to its function. This application aims to facilitate library visitors in searching for books, borrowing books, and returning books so that these activities become more organized. The function of the system created to process data related to the library such as managing book data, tracking book locations, checking borrowing, borrowing time limits to related fines. Then in the admin section it also functions for member registration activities, book data, book categories, book location data, book borrowing processes, book returns and data recap reports.